Evidence summary for pain management during retinopathy of prematurity screening - Tao, Chunlan; Tang, Jinghua; Tu, Jing; Li, Yongli; Chen, Yuqin (Frontiers in Pediatrics, 2026)
BackgroundRetinopathy of prematurity (ROP) is one of the leading causes of childhood blindness. Routine ROP screening in high–risk preterm infants is a fundamental and effective measure to prevent ROP; however, this screening process could cause pain to infants. This study aims to summarize the best evidence for pain management during ROP screening and provide a reference for the clinical practice of medical staff.MethodsWe systematically searched the literature on pain management during ROP screening, including clinical practice guidelines, evidence summaries, systematic reviews, meta–analyses, clinical decision support tools, and expert consensus statements. The search period was from inception to 31 October 2024. Four reviewers independently evaluated the quality of guidelines, and two reviewers independently assessed the quality of systematic reviews and expert consensus statements. Subsequently, evidence was extracted and graded.ResultsEighteen articles were included: six guidelines, three clinical decision support tools, six systematic reviews, and three expert consensus statements. 92 pieces of evidence were extracted and categorized into five dimensions: multidisciplinary pain management teams for ROP screening, pain assessment, non–pharmacological interventions, pharmacological interventions and pain documentation. Twenty–five evidence–based recommendations were finally formulated.ConclusionThe best evidence–based strategies for pain management during ROP screening in preterm infants provide actionable guidance for clinical practice. Medical staff should strengthen training in neonatal pain management and implement combined pharmacological and non–pharmacological interventions to alleviate procedural pain during ROP screening.